Impact of organizational leadership styles and employee-organization relationship on internal reputation: a conceptual framework - Ling, Hooi Lee; Abdullah, Zulhamri (Asian Scholars Network, 2023)
This paper proposes a conceptual framework that bridges the concept of internal reputation with organizational leadership and relationship perspectives using the lens of stakeholder theory. A cross-disciplinary literature review is carried out on positive organizational leadership styles, including transformational, authentic, and ethical leaderships, which predict internal reputation among employees, as well as the moderating function of employee-organization relationship in the said relationships. Four propositions are advanced from the review and an integrative conceptual framework is developed. The framework outlines leadership styles which practitioners, especially from the service sector, can consider to adopt in their organizations to enhance internal reputation perceptions on the basis of value creation. The proposed framework also advances the theoretical basis of effectively managing internal reputation from the stakeholder perspective.